2011
DOI: 10.1530/rep-10-0468
|View full text |Cite
|
Sign up to set email alerts
|

Reduced signaling through the hedgehog pathway in the uterine stroma causes deferred implantation and embryonic loss

Abstract: The role of the hedgehog (HH) signaling pathway in implantation was studied in mice in which the HH signal transducer, smoothened (SMO), was conditionally deleted in the stromal compartment of the uterus, using CRE recombinase expressed through the Amhr2 -mutant mice, Smo mRNA in uterine stroma was reduced 49% compared to that in Amhr2control mice, while levels in the luminal epithelium were not different. Litter size was reduced 60% in mutants compared with controls, but ovulation rate and the number of impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…This up regulation is indicative of the uterus being in a proliferative state in estrus. Ihh expression in the lumenal and glandular epithelium of the uterus increases in response to progesterone receptor signaling [73] and studies using transgenic mice showed that hedgehog signaling is essential for implantation [74]. The role of hedgehog signaling in the regulation of the reproductive cycle and the mechanisms of its interplay with other developmental pathways are only partially understood.…”
Section: Mouse Uterine Transcriptome In Estrus and Proestrusmentioning
confidence: 99%
“…This up regulation is indicative of the uterus being in a proliferative state in estrus. Ihh expression in the lumenal and glandular epithelium of the uterus increases in response to progesterone receptor signaling [73] and studies using transgenic mice showed that hedgehog signaling is essential for implantation [74]. The role of hedgehog signaling in the regulation of the reproductive cycle and the mechanisms of its interplay with other developmental pathways are only partially understood.…”
Section: Mouse Uterine Transcriptome In Estrus and Proestrusmentioning
confidence: 99%
“…In addition, secondary pathways and upstream regulators previously associated with endometrial receptivity were identified, such as: (i) The Hedgehog pathway (Fig. 2i), constituted by genes upregulated in PR cows, involved in implantation and early embryo development 49,50 . (ii) The ribosome KEGG pathways (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the other study indicated that both previous miscarriages and single nucleotide polymorphisms (SNPs) rs3738880 in Gli2 were associated with anorectal malformations, though the relationship between miscarriages and SNP rs3738880 in Gli2 remains unknown [54]. Besides, conditionally deleted of Smo in the mouse uterus impairs implantation and subsequent pregnancy loss [55].…”
Section: Discussionmentioning
confidence: 99%